The Effect of Kluwih (Artocarpus communis) Fruit Flesh Addition to the Nutrition Content of Mackerel Tuna Fish Abon - Abdullah, Nurlaila; Latief, Rindam; Bastian, Februadi; K.Sukendar, Nandi; Djalal, Muspirah; Restu Pala?langan, Melinda (Hasanuddin University Food Science and Technology Study Program, 2020)
One of the plants that are easily found in tropical country including Indonesia, but has not been used optimally is Kluwih fruit (Artocarpus communis). In fact, the fiber content in Kluwih is similar to meat that makes it good to be used as abon ingredient. Abon normally made of meat that makes the price generally high. To reduce the prices of abon to be affordable by the middle and lower classes, abon products can be made from vegetable ingredients (such as Kluwih) combined with meat. The research methods consisted of three treatments with different in the amount of Kluwih and Mackerel tuna fish ratio. We concluded that Kluwih fruit could be used as a substitute for meat in Abon making. The Kluwih addition in Fish Abon making affects the nutrition content of the Mackerel tuna abon final product significantly